Does Perceived Injury Explain the Effects of Gender on Attributions of Blame for Intimate Partner Violence? A Factorial Vignette Analysis - Parker, Maggie M. (Journal of family violence, 2022)
Perpetrator and victim gender influence how blame is assigned in intimate partner violence (IPV) scenarios. Although men’s differential capacity to inflict and sustain harm is posited as the reason male perpetrators and victims receive more blame for IPV, it is possible that other aspects of the construct of gender, such as gender role beliefs, underscore these effects. Using a sample of 323 college students and a factorial vignette design that varied body sizes and genders of victims and perpetrators, we examined the extent to which perceptions of physical injury accounted for the effects of perpetrator and victim gender on blame attributions, and whether adherence to traditional gender roles moderated any influences of gender unassociated with perceived injury. For female perpetrators, participants estimated lower levels of perceived injury and greater victim blame, with the former effect predominantly accounting for the latter. Male victims were viewed as less injured and more blameworthy, but the latter finding was not predominantly driven by injury perceptions. Perceived physical injury also did not account for why females perpetrating against males were blamed least. Controlling for differences in perceived injury, those holding more traditional gender views blamed victims of female violence more than victims of male-perpetrated violence. Notably, variations in body physical size were not associated with injury perceptions or blame attributions. These findings overall suggest that gender does influence blame attributions by way of perceived physical injury, but other aspects of the construct of gender are also relevant to these evaluations.